Fate and distribution of mercury during the desulfurization wastewater evaporation process. (15th June 2022) - Chen, Heng; Zhan, Lingxiao; Gu, Liyan; Zhou, Hao; Feng, Qianyuan; Wu, Hao; Zhao, Shilin; Yang, Linjun
Graphical abstract: Highlights: The gaseous Hg release process could be divided into three stages. Approximately 93.6% of Hg is released at an evaporation temperature of 300℃. The proportions of gaseous Hg 0 and Hg 2+ are sensitive to SO3 2- and Cl - contents. The potential risks of Hg release during the wastewater evaporation process are limited. Abstract: The wastewater evaporation technology was a promising method for desulfurization wastewater zero-liquid discharge. However, there is a risk of mercury release during wastewater evaporation, which may cause severe environmental issues. This work investigated the fate and distribution of mercury in the wastewater evaporation process. In the typical working conditions, 93.6% of Hg in the wastewater was released, and the rest part would retain in the final evaporation product. The gaseous Hg release process could be divided into three stages. The gaseous Hg 0 was the primary Hg released source in the initial evaporation process. Subsequently, due to the hydrolysis of chloride, the chlorine oxidizing atmosphere was generated, which induced the homogeneous oxidation of Hg 0 . At the end of evaporation, the pyrolysis of HgS and HgO would release a small amount of Hg. Besides, the effect of evaporation temperature, Cl - and SO3 2- content on Hg release was investigated. The higher evaporation temperature was adverse to Hg stability. The proportion of gaseous Hg 0 and Hg 2+ was highly sensitive to the SO3 2- and Cl - content. In addition, obtained from the risk assessment, the Hg release from the wastewater evaporation would not affect either total Hg content in main flue gas or solid-phase comprehensive utilization.